Correlation processing of incoherent scattering signal using multichannel device - Emelyanov, L.Ya.; Pulayev V.А.; Rogozhkin, E.V. (Radiotekhnika, 2018)
A method of correlation processing and the appropriate structure of the updated correlator operating as a part of the incoherent scatter radar in real time are proposed. The use of additional correlation channels makes it possible to reduce the error in determining the autocorrelation functions of the incoherently scattered signal and, as a consequence, to improve the accuracy of ionosphere parameters measurement without degrading height and temporal resolutions.